Effect of nano silica on the sinterability of hydroxyapatite dense bodies - Ranna, Tolouei; C.Y., Tan; S., Ramesh; Iis, Sopyan; W.D., Teng (Trans Tech Publications, Switzerland, 2011)
The effects of adding a small amount of nano silica in hydroxyapatite (HA) on the sinterability and mechanical properties of hydroxyapatite were studied. The starting HA powder was synthesized using a novel wet chemical precipitation method. Different amount of silica powder was mechanically mixed with the synthesized HA. The green samples were subsequently cold isostatically pressed at 200 MPa. Sintering in air was accomplished by firing the green samples at temperatures ranging from 1050°C to 1250°C. Sintered samples were analyzed to determine phase composition and mechanical properties. The XRD analysis revealed that with increasing the amount of silica in the HA powder, decomposition of HA to TCP occurred at sintering temperature higher than 1050°C. The bulk density of all silica-doped samples decreased through the temperature range studied. In agreement with the bulk density trend, the increasing silica additives in HA depleted the Young’s modulus and Vickers hardness of the HA body. The study revealed that the addition of silica have an adverse effect on the sintered properties of hydroxyapatite bioceramics.